Applications of Mittag-Leffer Type Poisson Distribution to a Subclass of Analytic Functions Involving Conic-Type Regions - Muhammad Ghaffar Khan; Bakhtiar Ahmad; Nazar Khan; Wali Khan Mashwani; Sama Arjika; Bilal Khan; Ronnason Chinram (Journal of Function Spaces)
In this article, we introduce a new subclass of analytic functions utilizing the idea of Mittag-Leffler type Poisson distribution associated with the Janowski functions. Further, we discuss some important geometric properties like necessary and sufficient condition, convex combination, growth and distortion bounds, Fekete-Szegö inequality, and partial sums for this newly defined class.